Ablation of sarcolipin decreases the energy requirements for Ca2+ transport by sarco(endo)plasmic reticulum Ca2+‐ATPases in resting skeletal muscle. Issue 11 (27th April 2013) - Bombardier, Eric; Smith, Ian C.; Vigna, Chris; Fajardo, Val A.; Tupling, A. Russell
Abstract : The purpose of this study was to examine the effects of sarcolipin (SLN) on sarco(endo) plasmic reticulum Ca 2+ ‐ATPase (SERCA pump) energetics in vivo and resting skeletal muscle metabolic rate. Using SLN knockout ( Sln −/− ) mice we show that SLN ablation increases the transport stoichiometry of SERCA pumps (Ca 2+ uptake/Ca 2+ ‐ATPase activity) and decreases the relative contribution of SERCA pumps to resting oxygen consumption ( VO 2 ) in soleus without affecting soleus or whole body VO 2 . These data suggest that the lower energy requirements for Ca 2+ cycling in resting skeletal muscle of Sln −/− mice do not impact significantly either skeletal muscle or whole body metabolic rate. Abstract : SLN ablation reduces slippage and back‐inhibition of SERCA pump activity. SLN ablation increases the efficiency of SERCA pumps in vivo. SLN ablation reduces ATP consumption by SERCA pumps in resting soleus muscle. Resting muscle and whole body VO2 is not significantly altered by SLN ablation.